Andragogical approach as a theoretical and methodological basis for the development of the pedagogical potential of a specialist - Palchyk, Henadzi V. (University Pedagogical Journal, 2026)
This article discusses the potential of pedagogical master’s programmes as a means of training specialists for the faculty of higher education institutions. It presents an analysis of the theoretical and methodological foundations, current trends, models, and organisational and pedagogical conditions necessary for the effective development of a system for training research and teaching staff in master’s programmes. An andragogical approach is considered as a key methodological basis for training teachers at the advanced level of higher education.
Keywords: higher pedagogical education; master’s programme; andragogical approach; training specialists